Changing Facet of Supply Chain Management – Is Human Factor No More Relevant? – A Study on Developing Countries - Vikas Gupta (International Journal of Supply Chain Management, 2023)
AbstractThe world is getting rapidly digitized in every aspect. Supply chains across industries and geographic locations must also adopt the new technologies that replace human labor in order tor remain relevant and functional. That is not to say that the need for human labor is completely non-existent. For developing and emerging economies, where the extent of digitization is still dismally low because of various factors, the relevance of the human facet of Supply Chain Management (SCM) is still hugely relevant and essential. This article investigates the importance of the human factor in the management of digitized supply chain in the modern world, from the perspective of the developing countries. The research reveals that there is no substitute for human labor, especially in situations where there is need for speed in decision making and where computer programs run on historical knowledge become incapable of offering a solution. Key words: digitization, supply chain, supply chain management, human, labor, RPA, AI, ML, labor displacement.